Dermoscopy in the Diagnosis of Cutaneous Leishmaniasis - Gamze Serarslan (Mattioli1885, 2019)
Background: Cutaneous leishmaniasis (CL) is a protozoan infectious disease. Dermoscopy is a noninvasive diagnostic tool that has been applied to several skin diseases, including infestations.